AKAR TEOLOGI-POLITIK GERAKAN RADIKALISME ISLAM DAN TERORISME DI INDONESIA - Ibi Satibi (UIN Mataram, 2023)
The issue of Islamic radicalism and terrorism in Indonesia in the last three decades has become a very serious problem. Not only in Indonesia, the phenomenon of terrorism in the Islamic world appears as an expression of the political movement of some Muslims who make use of Islamic doctrines, political attitudes and political movements that tend to be radical and extremist. By utilizing qualitative research procedures and data collection techniques through library research, this article draws several conclusions. First, international radicalism network named Al-Qaedah and Al-Jama’ah Al-Islamiyyah have influence over terrorist network in Indonesia and other Islamic worlds. The actors are alumni of the Afghan war and a network that been fostered since the 1970s through Al-Jamaah Al-Islamiyyah. Second, contemporary Islamic radicalism and terrorism movements in Indonesia have ideological-political connections with transnational Islamic movements and ISIS in two orientations namely the khilafah and the Islamic daulah. Third, in the socio-political area, a literalist understanding of the texts to fundamentalism. Finally, Islam often becomes a political commodity. Islamic doctrine often become tools to gain power of conversely also become tools to fight against power. This article recommends that the Indonesian government support moderate Islamic movements as counter-radicalism and terrorism measure.